2022
DOI: 10.1155/2022/7832564
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Predictive Value of Perioperative Cytokine Levels on the Risk for In‐Stent Restenosis in Acute Myocardial Infarction Patients

Abstract: To investigate the value of perioperative cytokine levels in predicting the risk for in-stent restenosis in patients with acute myocardial infarction. 452 patients with acute myocardial infarction admitted to our hospital between June 2018 and June 2020 were prospectively selected as subjects. All patients underwent percutaneous coronary intervention. The baseline data of the patients were collected. Venous blood was taken before, 24 hours, and 3 days after the operation to detect the levels of related cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%